(untitled) (ESMAT Magazine, 2025)
The object of this study is the fundamental right to the inviolability of the home and its exceptions in the context of the actions of public security agencies, which require control by several institutions. Contemporary constitutionalism has undergone significant development in the 20th century, seeking to limit administrative and judicial discretion, and in recent decades, the interface between law and public policies has been an important field of study for the effectiveness of fundamental rights. In order to limit the state’s punitive power in the area of ​​public security, it is essential to control police actions in their daily and effective performance. This article proposes to investigate home inviolability as a public policy problem, with a special focus on the problem of home entry in the event of flagrant crime, using the methodological tool of Isabela Ruiz and Maria Paula Dallari Bucci’s Framework of Public Policy Problems (2019) to analyze the normative and institutional challenges involved. The proposed analysis highlights the importance of rethinking public security practices from the perspective of fundamental rights, promoting public policies that respect human dignity and combat the structural inequalities so present in the Brazilian context.